Development of the voluntary health insurance market in Ukraine - Olena Zhuravka; Katherina Daher; Irina Bosak (Health Economics and Management Review)
This paper is aimed to study the development trends of the domestic voluntary health insurance market. The authors analyzed the current state of the domestic voluntary health insurance market by its types. In the study framework, the main tendencies were determined, while the relative ratios of voluntary health insurance market functioning were calculated. Health insurance has a great potential to be a promising source of additional funding for medicine in Ukraine. However, the systematization of scientific sources indicated that unresolved issues of further development of health insurance and the search for effective external funding sources for medicine in Ukraine, one of which may be the market of voluntary health insurance. This research's urgency consists of insufficient healthcare budgetary funding and low healthcare quality, provoking external funding sources' growth in national healthcare facilities such as voluntary health insurance. The study of the features of the voluntary health insurance market development was carried out in the following logical sequence: determining the relevance of the research topic; investigating the scientific background on the research topic; establishing the methodological basis; analyzing the indicators of voluntary medical insurance market development; considering the structure of health funding sources in Ukraine and some countries of Eastern Europe. The authors determined a need to develop voluntary health insurance in Ukraine as an external health funding source based on the findings. The conclusions and recommendations were formed. The study involved the methods of deduction and induction, analogy and comparative analysis, graphical method, method of statistical comparison. The research object is the voluntary health insurance market in Ukraine. The research period is 2012-2020. The obtained results indicated that the voluntary health insurance market is undoubtedly an essential component of the Ukrainian insurance market. The authors noted that it is an effective additional way for actual funding the social needs in medicine. Therefore, it calls for further in-depth study and more attention from the population. The results of this study could be helpful for scientists, health and insurance professionals.